The role of Target Cost Technology and Value Stream in Reducing Costs - Ass. Pro . Dr. Mohammed Abdul Wahid Flayyih; Ass . Lec . Shaymaa Majeed Saeed (Scholars Digest Publishing, 2023)
The research aims to clarify the knowledge bases of target costing and value stream technology, and explain how to reduce costs after applying target costing and value stream techniques in the research sample company. Where the target cost and value flow technology was used to reduce the costs of the specialized diesel oil product MG 154, as the economic units were adopted on traditional methods and techniques in determining selling prices, which depend on adding a margin after calculating the costs, which are not in line with the developments taking place, in addition to the high Production costs, which is based on traditional concepts that stand as an obstacle to achieving the objectives of the unit, and the findings of the researchers in the practical aspect when applying. With the target costing technique, costs were clearly reduced, as the percentage of total annual production decreased by 2.5%, i.e. by 226,734,828 dinars. However, when applying the value flow tool, workers' wages costs were reduced (23,285,603.6) dinars, while waiting time costs were reduced (253,663,200) dinars, which was reflected as a result of cost reduction ,
Keywords: target cost, value stream, cost reduction.